Innovations for teaching and learning: An exploration of the potential of EEG for individual and group learning activities - Roslan, N.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
Group based learning or also known as collaborative learning has been in practice until now as one of the methods of learning as it can help learners gain better learning achievements especially in problem solving tasks. However, to date, many learning institutions from elementary level all the way to tertiary level are mostly practicing teaching approach based on lecture only which is a one-way teaching method that does not involve significant student participation. It is thus important to investigate objectively the learning achievement of group and individual learning in meeting their learning needs. Hence, this study explores the potential of EEG to investigate the learning achievements between group and individual learning in problem solving task as EEG is widely been used for investigation of brain behavior in diversity of cognitive tasks including problem solving. We will investigate brain activation in individual and group learning and the differences between them based on problem solving task using EEG. Â© 2015 IEEE.